A violência e o desenvolvimento moral nos jogos eletrônicos - COSTA, Jonatas Araújo da (2024)
The electronic games have surpassed their original expectations of pure amusement, and now they are a symbiotic part of a technology-driven society and must be explored in their entirety as a cultural artifact. In view of the need for studies aimed at electronic games and considering the importance of them as one of the protagonists of technology and postmodern culture, the present work seeks to provide a discussion on the aspects that contribute to moral engagement in short-term decision moral choices in electronic games; as opposed to the understood factors that underlie moral disengagement in games. Therefore, the work proposes the use of theoretical models that build upon the moral disengagement model, and self-determination theory to assess moral involvement in games, addressing technical points of mechanics and gameplay, in addition to moral choices in games with interactive narrative.